2012
DOI: 10.1161/hypertensionaha.111.188813
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Healthcare Utilization Among Children and Adolescents With Hypertension in the United States

Abstract: The objective of this study was to evaluate the healthcare utilization of hospitalized children with hypertension. The Healthcare Cost and Utilization Project Kids' Inpatient Database, years 1997, 2000, 2003, and 2006, was used to identify hypertension hospitalizations. We examined the association of patient and hospital characteristics on hypertension charges. Data from each cohort year were used to analyze trends in charges. We found that 71282 pediatric hypertension hospitalizations generated $3.1 billion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
(28 reference statements)
2
24
0
1
Order By: Relevance
“…Hypertension used to be regarded as an adult disease with no real relevance to children, because pediatric hypertension was thought to be mostly attributed to secondary causes [7•], and because the economic impact of pediatric hypertension was so trivial as compared to costs related to adult hypertension [8,9]. If so, why should we be concerned about pediatric hypertension in Asian countries?…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension used to be regarded as an adult disease with no real relevance to children, because pediatric hypertension was thought to be mostly attributed to secondary causes [7•], and because the economic impact of pediatric hypertension was so trivial as compared to costs related to adult hypertension [8,9]. If so, why should we be concerned about pediatric hypertension in Asian countries?…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In a 10-year study from 1997 to 2006, Tran et al 5 observed significantly increasing occurrences in hypertension visits among pediatric patients. The increasing incidences of pediatric hypertension, which appear to be associated with childhood obesity, are also associated with increasing health-care charges.…”
mentioning
confidence: 99%
“…Despite the vast discrepancy, however, the current report highlights the growing economic impact of pediatric hypertension. The current study by Tran et al 1 estimates that, between 1997 and 2006, the hospital costs to treat children with hypertension-related illness were more than $3 billion.…”
mentioning
confidence: 81%